Avoiding the Delusions of Today's Capitalism with a Thorough Understanding of Marxism as the Key. Issue 3 (3rd July 2022) - Nguyen, Minh Hoan
ABSTRACT: Between the early 1970s, when neoliberalism was in full swing and became the dominant rhetoric of the time, and the 2008 global economic crisis, capitalism as a result of its inherent nature entered a fundamental crisis with unavoidable consequences. Many in-depth analyses of the economic crisis from a Marxist viewpoint have revealed that in the area of wealth appropriation, capitalism has now exacerbated inequality to absurd levels. This is not to mention other challenging issues such as the parasitic nature of increasingly digitized finance capital, uncontrolled inflation leading to rampant financial deficits, the worsening ecological crisis with mounting environmental costs that erode profits, escalating political manipulation by monopoly capitalists, and the mounting by developed countries of inappropriate military interventions in the developing world, to name just a few. Today, the fundamental characteristics and specific manifestations of contemporary capitalism are exerting significant impacts on the process of building socialism worldwide. Faced with today's capitalism, China and Vietnam while exercising due caution must put forward and consistently highlight the need to examine the direction the system is taking. Thorough research on this subject is critical for a correct scientific understanding.